Rapid Determination of Moisture Content of Soil Using Microwave Oven - Ghosh, Barnali (AMC Indian Journal of Civil Engineering, 2023)
Generally, moisture content of soil is determined by heating the soil sample in a hot air oven. As per IS 2720, it takes 24 hrs time at 105°C + – 5°C. The present study shows that a microwave oven is more convenient in determining the water content as it takes much lesser time than conventional hot air oven. A known quantity of water is added to 25 g and 50 g of dry soil for this. The samples with known water content are then heated in microwave oven for 5, 10, 15 and upto 30 minutes for every 5 minutes interval. Water content determined from microwave woven heating is compared with conventional oven water content. Many experiments are conducted with black cotton soil as well as red sandy soil with different water content and it is seen that the results are similar. Thus, we can state that water content can be found out by using a microwave oven and the results are as accurate when we conduct the tests as per IS 2720 Part II and the experiments takes much lesser time. Hence, we can recommend it as an alternate method of determining water content rapidly. It costs much less as power consumption and initial installation cost is less.